Vasyl Semenovych Tkachenko is a classic of Ukrainian steppe studies (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
The Ukrainian school of steppe studies, which was started at the beginning of the last century, has a number of scientific discoveries associated with the names of outstanding scientists - Y.K. Pachosky, G.I. Tanfilieva, H.M. Vysotskyi, E.M. Lavrenka, N.O. Desyatova-Shostenko, F.Ya Levinoi, O.I Sokolovskyi, M.S. Shalita, Yu.D. Kleopova, G.I Bilyka, V.V. Osychnyuk and many others who defined new paths and horizons of its development. Among its leaders, the academic figure Vasyl Semenovych Tkachenko occupies a prominent place, who on September 3 of this year turns 85 from the day of his birth and 60 years of scientific activity. The results of the study of Vasyl Semenovych's scientific achievements and socio-ecological activities give reasons to consider him one of the most prominent figures of modern steppe studies. Basic education, breadth and flexibility of views on global and local environmental problems, logic and discipline of thinking, intellectual self-sufficiency, firm ethical principles combined with a certain degree of non-conformism, content of personal experience and valeological endurance made it possible to formulate and implement strategic guidelines in the field of development of the national steppe studies. He laid the foundations of phytocenotic and cartographic monitoring of protected steppes, on the basis of which the specificity and functional essence of the reserve structurogenesis of grass ecosystems, its phasing and homeostatic orientation were determined. His research within the steppe belt of Ukraine is quite well-known, in particular, on the reasons for the shallowing of small rivers in the Donbass and on measures to optimize the environment of its area, on the development of classification and detailed geobotanical zoning, on the ecological justification of the projected Danube-Dnipro water management complex, on the representativeness of the network of nature conservation areas in the steppe zone, its optimization, etc. The contribution of V.S. Tkachenko was involved in nature conservation, and with his participation, the protection council of protected areas and nature reserves was organized, a number of steppe species were described in the editions of the "Red Book of Ukraine" and rare phytocenoses in the "Green Book of Ukraine".
Keywords: bibliography, botany, steppe, Ukraine.